he Impact of Expatriate Remittances on Economic Growth In the Kingdom of Saudi Arabia - Almosabbeh, Imadeddin (The Arab Journal of Administration, 2022)
This study seeks to uncover the nature of the relationship that expatriate labor remittances have in the economic growth of Saudi Arabia. Autoregressive Distributed Lags (ARDL) and Non-Linear ARDL (NARDL) are used as a method to discover the influence and nature of the remittances on Saudi GDP growth. This method, NARDL, enables us to detect whether the relationship between the expatriate labor remittances and Economic growth is symmetric or asymmetric. This Study depending on data collected from the World Bank, Saudi Central Bank (SAMA), and the Saudi General Authority of Statistics to cover the period 1970-2016. The study concludes that the relationship between labor remittances and Saudi Arabian economic growth is asymmetrical; a one percent decrease in remittances increases GDP by 0.837 percent, while a one percent increase in remittances increases GDP by 0.291 percent. This study recommends that the Kingdom of Saudi Arabia continue to maintain remittances at least their current level.